EVALUATION OF SHORT TERM TOXICITIES INDUCED BY GINGER 0LEORESIN (Biological Sciences - PJSIR, 2002)
Ginger Oleoresin  exhibited  a marked  action on central  nervous  system.  The oleoresin was found to be non  lethal upto a  dose of 3.0g kg·1., while a dose above that resulted in mortalities. The LDSO was found to be 6.284 g kg- 1 . The signs and symptoms observed in non lethal doses were solely functional and short lived. The magnitude and intensities of sign s and symptoms exhibited were found to be dose dependant, while lethal  doses  im parted  pharmacological  and  toxicological  action by affecting the physiological mechanism of the body. Death occurred may be due to the direct action on  central  nervous  system  resulting  in  respiratory  failure  as well  as circulatory arrest.